Environment-friendly graphite crystallizer release agent as well as preparation method and application thereof

By using environmentally friendly graphite crystallizer release agent prepared with materials such as saturated fatty alcohol esters, the problems of poor environmental protection and easy decomposition of traditional mold release agents are solved, and the effect of reducing wear and extending the service life of graphite crystallizers is achieved.

CN119505982APending Publication Date: 2025-02-25ZHENGZHOU OPTRIS SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411708679.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional graphite crystallizers have poor environmental protection and are easy to decompose at high temperatures, resulting in corrosion of graphite crystallizers and shortening their service life.

Method used

Saturated fatty alcohol esters are used as base oils, combined with viscose, friction reducing agent, surfactant and antioxidant to form an environmentally friendly graphite crystallizer release agent. The release agent reduces wear of the graphite crystallizer by forming a continuous oil film with good adhesion and maintains a stable lubrication effect at high temperatures.

Benefits of technology

It effectively reduces the wear of graphite crystallizers and the formation of high-temperature deposits, extends the service life of graphite crystallizers. At the same time, due to the biodegradability and non-toxicity of the material, it is an environmentally friendly new material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505982A_ABST
    Figure CN119505982A_ABST
Patent Text Reader

Abstract

The invention provides an environment-friendly graphite crystallizer release agent as well as a preparation method and application thereof, and relates to the field of graphite crystallizer release agents. The environment-friendly graphite crystallizer release agent comprises the following components: 3%-7% of a viscosity index improver, 1%-4% of a friction reducing agent, 0.5%-1.2% of a surfactant, 0.3%-0.8% of an antioxidant and the balance of base oil, wherein the base oil is saturated fatty alcohol ester. The preparation method comprises the following steps: uniformly mixing the raw material components, stirring and heating to 60 DEG C, and continuously stirring for 20 minutes at the temperature, thereby obtaining the product. The environment-friendly graphite crystallizer release agent has ultra-low friction coefficient and friction force, and abrasion of a crystallizer in the using process can be reduced; the environment-friendly graphite crystallizer release agent further has good detergency and ultralow high-temperature coking tendency, and formation of high-temperature sediments can be reduced. The main substance base oil has biodegradability, and no toxic substance is generated after high-temperature volatilization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of graphite crystallizer release agents, and is mainly used for casting demolding of non-ferrous metals and non-ferrous metal alloys, and in particular to an environmentally friendly graphite crystallizer release agent and a preparation method and application thereof. Background Art

[0002] In the metal casting industry, the crystallizer is a key process equipment, and its performance directly determines the surface quality, internal structure and production efficiency of the ingot product. Although traditional crystallizer materials, such as steel or copper crystallizers, have played an important role in previous production, they are difficult to meet the increasingly stringent requirements of modern industry for ingot quality due to their limitations in thermal conductivity, wear resistance and corrosion resistance. Therefore, graphite crystallizers have gradually become the mainstream choice to replace traditional crystallizers due to their excellent thermal conductivity, good self-lubrication and chemical stability.

[0003] During the use of graphite crystallizers, mold release agents play a vital role, which directly affects the surface quality of the product, production efficiency and mold maintenance costs. Traditional mold release agents often contain volatile organic compounds (VOCs) that are harmful to the human body, which not only pollutes the environment but also may endanger the health of operators. In addition, some mold release agents are easy to decompose at high temperatures, resulting in reduced mold release effects and even corrosion of the graphite crystallizer, shortening its service life. Therefore, it is particularly important to develop a graphite crystallizer release agent that is both environmentally friendly and efficient. Summary of the invention

[0004] In order to improve the problem that the current release agent has poor environmental protection and is easy to decompose at high temperature, causing corrosion to the graphite crystallizer, the present application provides an environmentally friendly graphite crystallizer release agent and a preparation method and application thereof.

[0005] In the first aspect, the present application provides an environmentally friendly graphite crystallizer release agent, which adopts the following technical solution: An environmentally friendly graphite crystallizer release agent comprises the following components by mass percentage: 3% to 7% viscosity modifier, 1% to 4% friction reducer, 0.5% to 1.2% surfactant, 0.3% to 0.8% antioxidant, and the rest is base oil, wherein the base oil is saturated fatty alcohol ester.

[0006] The present application adopts saturated fatty alcohol ester as base oil. The polar part in saturated fatty alcohol ester can interact with the non-polar carbon atoms on the graphite surface through van der Waals force, so that the saturated fatty alcohol ester molecules can approach and adsorb on the graphite surface to form a continuous molecular oil film with good adhesion. This oil film not only has good adhesion, but also can effectively isolate the direct contact between graphite and castings, thereby reducing the wear of graphite crystallizers. Moreover, saturated fatty alcohol ester has extremely high thermal oxidation stability, high flash point, low volatility and other characteristics, which can effectively reduce the formation of carbides in the contact area between the casting liquid and the graphite plate. In addition, the base oil system is biodegradable, and no toxic substances are generated after high-temperature volatilization, which belongs to an environmentally friendly new material.

[0007] Optionally, the following components are included, calculated by mass percentage: 5% viscosity modifier, 2% friction reducer, 1% surfactant, 0.5% antioxidant, and the rest is base oil.

[0008] The present application further optimizes the formula of the release agent, and the proportions of the components are moderate and synergistic with each other. The release agent can form a continuous, uniform and well-adhesive oil film on the surface of the graphite crystallizer, effectively reducing wear and friction and improving demoulding efficiency.

[0009] Optionally, the base oil is pentaerythritol ester formed by the reaction of pentaerythritol and saturated fatty acid.

[0010] Furthermore, the saturated fatty acid may be one or more of pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, and decanoic acid.

[0011] Pentaerythritol ester has excellent extreme pressure performance and oxidation resistance, can maintain a stable lubrication effect at high temperatures, and effectively prevent the graphite crystallizer from sticking or being damaged during high-temperature casting.

[0012] Optionally, the viscosity modifier is polyisobutylene with a molecular weight of 600-700.

[0013] The viscosity modifier uses low molecular weight polyisobutylene, which can effectively reduce the formation of oil smoke in high temperature environment, and no residue is left after volatilization. At the same time, low molecular weight polyisobutylene has a certain cleanliness, reduces the generation of high temperature carbon deposits, and its anti-wear performance is also relatively outstanding, which can effectively reduce the wear of graphite crystallizers. In addition, low molecular weight polyisobutylene can improve the lubricating properties of lubricating oil, reduce friction and loss, and no residue is left after high temperature volatilization, which reduces the formation of carbon deposits, reduces equipment energy consumption, and extends service life.

[0014] Optionally, the friction reducer is a phosphorus-nitrogen compound.

[0015] The friction reducer uses ashless phosphorus-nitrogen compounds, does not contain any metal, has outstanding anti-wear and anti-rust properties, and has a low dosage. When combined with low molecular weight polyisobutylene, it can greatly reduce the friction coefficient. At the same time, it has no irritating odor at high temperatures, and has good oil solubility and storage stability.

[0016] Optionally, the surfactant is a polyetheramine.

[0017] During the casting process, the crystallizer graphite plate is in contact with the high-temperature casting liquid for a long time, which easily forms high-temperature deposits in the micropores of the graphite plate. Polyetheramine molecules contain both polar groups and non-polar groups. The polar groups extend into the micropores of the graphite plate, surround the tiny particles in the formed deposits, form oil-soluble micelles, and disperse into the oil. During the demolding process, as the temperature of the crystallizer graphite plate increases, the demolding agent in the graphite plate overflows, and the demolding agent wrapped in the tiny deposits will burn a part at this time to achieve the purpose of cleaning. At the same time, its non-polar groups are preferentially adsorbed on the surface of the graphite plate, forming a layer of molecular protective film to prevent the aggregation and deposition of particles or adhesion on the graphite plate, which plays a role in keeping it clean.

[0018] Moreover, polyetheramine has excellent detergency and has extremely strong cleaning and solubility ability for asphaltene, colloid and precipitates.

[0019] Optionally, the antioxidant is an amine antioxidant.

[0020] The antioxidant is an amine antioxidant, which can prevent or inhibit the chain initiation reaction and chain growth reaction by capturing peroxyl free radicals in a high temperature environment, thereby terminating the free radical chain reaction and achieving the purpose of preventing oxidation. Amine antioxidants have high temperature antioxidant properties, extend the oxidation induction period, and inhibit the formation of precipitates.

[0021] In a second aspect, the present application provides a method for preparing an environmentally friendly graphite crystallizer release agent, using the following technical solution: A method for preparing an environmentally friendly graphite crystallizer release agent comprises the following steps: First, the raw material components are mixed evenly, stirred and heated to 60° C., and stirred continuously at this temperature for 20 minutes to obtain the environmentally friendly graphite crystallizer release agent.

[0022] The preparation method of the graphite crystallizer release agent of the present application has a simple process, does not require complicated equipment and process conditions, and is easy to implement in industrial production. At the same time, the shorter preparation time and lower temperature requirements also reduce energy consumption and production costs.

[0023] In a third aspect, the present application provides an application of an environmentally friendly graphite crystallizer release agent in a graphite crystallizer.

[0024] By using the graphite crystallizer release agent of the present application, wear on the surface of the graphite crystallizer can be avoided and its service life can be extended.

[0025] In summary, the present application includes at least one of the following beneficial effects: The environmentally friendly graphite crystallizer release agent of the present application has an ultra-low friction coefficient and friction force, so it can reduce the wear of the crystallizer during use; in addition, the environmentally friendly graphite crystallizer release agent of the present application also has good cleanliness and ultra-low high-temperature coking tendency, which can reduce the formation of high-temperature deposits. At the same time, the main material base oil in the present application is biodegradable, and no toxic substances are generated after high-temperature volatilization. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a comparison chart of liquid phase corrosion results of the environmentally friendly graphite crystallizer release agents of Examples 1-3 of the present application and the graphite crystallizer release agent of Comparative Example 1; Figure 2 It is a comparison chart of the high temperature gelling tendency results of the environmentally friendly graphite crystallizer release agents of Examples 1-3 of the present application and the graphite crystallizer release agent of Comparative Example 1; Figure 3 It is a comparison chart of the friction coefficients of the environmentally friendly graphite crystallizer release agents of Examples 1-3 of the present application and the graphite crystallizer release agent of Comparative Example 1 in the friction reduction performance test; Figure 4 This is a friction comparison diagram of the environmentally friendly graphite crystallizer release agents of Examples 1-3 of the present application and the graphite crystallizer release agent of Comparative Example 1 in the friction reduction performance test; Figure 5 This is a graph showing the wear spot performance results of the environmentally friendly graphite crystallizer release agent of Example 1 of the present application in a friction reduction performance test; Figure 6 This is a graph showing the wear spot performance results of the environmentally friendly graphite crystallizer release agent of Example 2 of the present application in a friction reduction performance test; Figure 7 This is a graph showing the wear spot performance results of the environmentally friendly graphite crystallizer release agent of Example 3 of the present application in a friction reduction performance test; Figure 8 This is a graph showing the wear spot performance results of the graphite crystallizer release agent of Comparative Example 1 of the present application in the friction reduction performance test; Fig. 9 This is a comparison chart of average wear spot diameters of the environmentally friendly graphite crystallizer release agents of Examples 1-3 of the present application and the graphite crystallizer release agent of Comparative Example 1 in a friction reduction performance test; Fig.10 This is a state diagram of a product actually produced after demoulding using the environmentally friendly graphite crystallizer release agent of Example 1 of the present application; Fig.11This is a state diagram of a product actually produced after demoulding using the environmentally friendly graphite crystallizer release agent of Example 2 of the present application; Fig.12 This is a state diagram of a product actually produced after demoulding using the environmentally friendly graphite crystallizer release agent of Example 3 of the present application; Fig.13 This is a state diagram of the product after demolding which is actually produced using the graphite crystallizer release agent of comparative example 1 of the present application. DETAILED DESCRIPTION

[0027] The technical solution of the present application will be described in detail below in conjunction with specific embodiments and drawings.

[0028] The base oil used in the following examples is pentaerythritol alcohol ester POE produced by Yingkou Xinghuo Chemical Co., Ltd., with a specification of PE451 and a kinematic viscosity of 25.0 mm at 40°C. 2 / s, kinematic viscosity at 100℃ is 5.0 / mm 2 / s, viscosity index (VI) is 130, pour point is -60°C, open flash point is 255°C, and acid value is 0.05 mgKOH / g.

[0029] The viscosity modifier used in the following examples is polyisobutylene from Shanghai Qicheng Lubrication Technology Co., Ltd., specification H-25, molecular weight of 635, kinematic viscosity at 100°C of 54.5 mm 2 / s, open flash point is 212℃, pour point is -23℃, specific gravity (15.5℃) is 0.869, and bromine value is 27gBr2 / 100g.

[0030] The friction reducer used in the following examples is a phosphorus-nitrogen compound from Suqing (Tianjin) Rubber & Plastic Products Co., Ltd., with a specification of MQ 3490, a density (20°C) of 0.90 kg / m3, a kinematic viscosity at 100°C of 10.0 mm2 / s, a closed cup flash point of 142°C, a phosphorus content of 2.5%, and a nitrogen content of 1.3%. It is an ashless dispersant and does not contain any metal.

[0031] The surfactant used in the following examples is a polyetheramine PEA from Tekodo Additives (Shenzhen) Co., Ltd., with a specification of FL A-200, a density (25°C) of 0.98 kg / m3, an open flash point of 230°C, a kinematic viscosity at 25°C of 325 mm2 / s, a pour point of -14°C, and a total amine content of 1.0 meq / g.

[0032] The antioxidant used in the following examples is octyl / butyl diphenylamine from Jinzhou Kangtai Petroleum Additive Co., Ltd., specification L557, density (20°C) of 0.96 kg / m3, open flash point of 160°C, kinematic viscosity at 40°C of 180 mm2 / s, nitrogen content of 4.5%, and diphenylamine content of 0.5%.

[0033] Example 1 provides an environmentally friendly graphite crystallizer release agent, which includes raw material components of the following formula: 3.0% viscosity modifier, 1.0% friction reducer, 0.5% surfactant, 0.3% antioxidant, and 95.2% base oil.

[0034] The preparation method is as follows: first, respectively add the viscosity modifier, friction reducer, surfactant, and antioxidant into the base oil in a mass ratio, stir and heat to 60°C, and continue stirring at this temperature for 20 minutes so that the various additives can be fully dissolved in the base oil. The product obtained after full dissolution is an environmentally friendly graphite crystallizer release agent.

[0035] Example 2 provides an environmentally friendly graphite crystallizer release agent, which includes raw material components of the following formula: 5.0% viscosity modifier, 2.0% friction reducer, 1.0% surfactant, 0.5% antioxidant, and 91.5% base oil.

[0036] The preparation method of Example 2 is the same as that of Example 1.

[0037] Example 3 provides an environmentally friendly graphite crystallizer release agent, which includes raw material components of the following formula: 7.0% viscosity modifier, 4.0% friction reducer, 1.2% surfactant, 0.8% antioxidant, and 87.0% base oil.

[0038] The preparation method of Example 3 is the same as that of Example 1.

[0039] Comparative Example 1 provides a prior art release agent, specifically CP-101 from Krupp.

[0040] Performance Testing The release agents of Examples 1-3 and Comparative Example 1 were tested for the following multiple items.

[0041] 1. Physical and chemical performance indicators The physical and chemical performance indicators of the release agents of Examples 1-3 and Comparative Example 1 were tested respectively with reference to the test items and corresponding test methods listed in Table 1. The test results are shown in Table 1.

[0042] Table 1 Physical and chemical index test results It can be seen from the results in Table 1 that the viscosity of the release agents of Examples 1-3 is improved compared with that of Comparative Example 1, and the viscosity index is improved, so that the viscosity-temperature performance of the oil is more prominent, thereby ensuring that more release agent will enter the mold when brushing, and at the same time, it can effectively prevent the release agent from volatilizing from the mold too early under high temperature conditions, thereby causing lubrication failure.

[0043] 2. Liquid phase corrosion performance test According to the liquid phase corrosion test method of GB 11143-2008, the release agents of Examples 1-3 and Comparative Example 1 were subjected to corrosion tests. The test results are shown in Table 2 and Table 3. Figure 1 shown. Figure 1 It is a comparison chart of the liquid phase corrosion results of the environmentally friendly graphite crystallizer release agents of Examples 1-3 of the present application and the graphite crystallizer release agent of Comparative Example 1. Among them, Figure a corresponds to the environmentally friendly graphite crystallizer release agent of Example 1, Figure b corresponds to the environmentally friendly graphite crystallizer release agent of Example 2, Figure c corresponds to the environmentally friendly graphite crystallizer release agent of Example 3, and Figure d corresponds to the graphite crystallizer release agent of Comparative Example 1.

[0044] Table 2 Liquid phase corrosion test results Test items Example 1 Example 2 Example 3 Comparative Example 1 Liquid phase corrosion (distilled water method) Rust-free Rust-free Rust-free Rust-free Although the results in Table 2 show that the liquid phase corrosion results of the release agents of Examples 1-3 and Comparative Example 1 are all rust-free, Figure 1 From the perspective of glossiness in the four figures, the steel rod of Comparative Example 1 is slightly dull, while the steel rods of Examples 2 and 3 have better glossiness.

[0045] 3. High temperature gumming tendency test The release agents of Examples 1 to 3 and Comparative Example 1 were tested for their tendency to form gum at high temperatures. The test conditions were homemade, and the samples were baked in a high-temperature test chamber. Test temperature: 280°C, oil sample: 1g, test time: 2h, test material: aluminum box, test results are shown in Figure 2 . Figure 2 It is a comparison chart of the high temperature gelling tendency results of the environmentally friendly graphite crystallizer release agents of Examples 1-3 of the present application and the graphite crystallizer release agent of Comparative Example 1. Among them, Figure e corresponds to the environmentally friendly graphite crystallizer release agent of Example 1, Figure f corresponds to the environmentally friendly graphite crystallizer release agent of Example 2, Figure g corresponds to the environmentally friendly graphite crystallizer release agent of Example 3, and Figure h corresponds to the graphite crystallizer release agent of Comparative Example 1.

[0046] from Figure 2 It can be seen from the results that the high-temperature gelling tendency of the release agents of Examples 1-3 is significantly better than that of Comparative Example 1, and the high-temperature gelling tendency of Example 2 is also significantly better than that of Examples 1 and 3, which plays a key role in extending the service life of the crystallizer and improving the quality of the casting products.

[0047] 4. Friction reduction performance test According to the test method for determining the anti-wear performance of lubricating oil in SH / T 0189-2017, the release agents of Examples 1 to 3 and Comparative Example 1 were tested for friction reduction performance. The test conditions are as follows: load 392N, speed 1200r / min, temperature 75°C, time 3600s. The results of the friction coefficient and friction force are compared in Figure 3 and Figure 4 , wear spot performance test see Figures 5 to 9 . Figure 5 This is a graph showing the wear spot performance results of the environmentally friendly graphite crystallizer release agent of Example 1 of the present application in a friction reduction performance test; Figure 6 This is a graph showing the wear spot performance results of the environmentally friendly graphite crystallizer release agent of Example 2 of the present application in a friction reduction performance test; Figure 7 This is a graph showing the wear spot performance results of the environmentally friendly graphite crystallizer release agent of Example 3 of the present application in a friction reduction performance test; Figure 8 This is a graph showing the wear spot performance results of the graphite crystallizer release agent of Comparative Example 1 of the present application in the friction reduction performance test; Fig. 9 It is a comparison chart of the average wear spot diameters of the environmentally friendly graphite crystallizer release agents of Examples 1-3 of the present application and the graphite crystallizer release agent of Comparative Example 1 in the friction reduction performance test.

[0048] Depend on Figure 3-4 It can be seen from the results that there is little difference between Example 1 and Comparative Example 1 in terms of friction force and friction coefficient performance. Figure 5-9 It can be seen from the results that in terms of the comprehensive performance of wear spots, Example 1, Example 3 and Comparative Example 1 are basically similar, but the comprehensive performance of Example 2 is significantly better than that of Comparative Example 1.

[0049] 5. Field use test In order to further verify the feasibility of the present application scheme, an aluminum processing enterprise in Zhengzhou used the release agents of Examples 1-3 and Comparative Example 1 to conduct actual production condition tests. Test conditions: furnace temperature at 700-740°C, ingot size: 1580×665×6320mm, material: 5052 high magnesium alloy. The state of the test product after demoulding is shown in Figures 10 to 13 .

[0050] Depend on Figures 10 to 13 Combined with the factory's requirements for the ingot pull marks after demolding, the release agents of Examples 1 to 3 and Comparative Example 1 can meet the production requirements. From the surface smoothness of the demolded products, it can be seen that Example 2 is significantly better than the other examples and Comparative Example 1.

[0051] Based on the above tests, the release agents of Examples 1 to 3 can completely replace Comparative Example 1; and Example 2 is significantly superior to Example 1 and Example 3 in terms of comprehensive performance indicators and on-site use conditions.

[0052] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. An environmentally friendly graphite crystallizer release agent, characterized in that: The composition comprises the following components by mass percentage: 3% to 7% of viscosity modifier, 1% to 4% of friction reducer, 0.5% to 1.2% of surfactant, 0.3% to 0.8% of antioxidant, and the rest is base oil, wherein the base oil is saturated fatty alcohol ester.

2. The environmentally friendly graphite crystallizer release agent according to claim 1, characterized in that: Calculated by mass percentage, it includes the following components: 5% viscosity modifier, 2% friction reducer, 1% surfactant, 0.5% antioxidant, and the rest is base oil.

3. The environmentally friendly graphite crystallizer release agent according to claim 1, characterized in that: The base oil is pentaerythritol ester formed by the reaction of pentaerythritol and saturated fatty acid.

4. The environmentally friendly graphite crystallizer release agent according to claim 1, characterized in that: The viscosity modifier is polyisobutylene with a molecular weight of 600-700.

5. The environmentally friendly graphite crystallizer release agent according to claim 1, characterized in that: The friction reducer is a phosphorus-nitrogen compound.

6. The environmentally friendly graphite crystallizer release agent according to claim 1, characterized in that: The surfactant is polyetheramine.

7. The environmentally friendly graphite crystallizer release agent according to claim 1, characterized in that: The antioxidant is an amine antioxidant.

8. A method for preparing an environmentally friendly graphite crystallizer release agent according to any one of claims 1 to 7, characterized in that: The steps include: First, the raw material components are mixed evenly, stirred and heated to 60° C., and stirred continuously at this temperature for 20 minutes to obtain the environmentally friendly graphite crystallizer release agent.

9. Use of the environmentally friendly graphite crystallizer release agent according to any one of claims 1 to 7 in a graphite crystallizer.